IDEALISME PENDIDIKAN PLATO - Fathoni, AB. MusyafaÂ’ (JURNAL TADRIS STAIN PAMEKASAN, 2010)
Abstract: Plato is one well-known Greek philosopher. His philosophical thoughts was strongly influenced by the ideas of Socrates because of his teacher.  The essence of Platos teachings is about the idea (the world of idea). In his view, there are two kinds of the world. The first, this world, which is observed with the senses. The second, the world of idea, a world that has no change, no plurality (in the term of the good is only one, and beauty is only one). It is eternal. The concepts of these ideas eventually affect Platos ideas about education.